Revitalization of Educational Information Media in Batur UNESCO Global Geopark Using QR-Code and Web-Based Augmented Reality - Ida Ayu Gde Suwiprabayanti Putra; I Gusti Ngurah Anom Cahyadi Putra; Gst. Ayu Vida Mastrika Giri; I Gede Surya Diva Ananda; Rahelita Pasaribu; Ida Bagus Oka Agastya; I Wayan Gobang Edy Sucipto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Batur UNESCO Global Geopark in Bali represents a significant natural and cultural heritage area with high educational value. However, the existing information delivery system primarily relies on static information boards, which are less effective in engaging visitors, particularly younger generations accustomed to digital technology. This community service project aims to revitalize educational information media in Batur Geopark through the integration of QR-code technology and Web-based Augmented Reality (WebAR). The implementation method includes needs analysis with geopark stakeholders, design of QR-code-based educational media, development of 3D models representing key geosite elements (Mount Batur, Kintamani dog, and Trunyan village), and integration into a WebAR platform accessible via smartphones. The system was evaluated through user testing involving students, tourists, and local communities to assess usability, accessibility, and learning effectiveness. The results demonstrate that the proposed system enhances user engagement and improves understanding of geological, ecological, and cultural information. The combination of QR-code and interactive 3D visualization provides a more immersive and flexible learning experience compared to conventional methods. Additionally, the approach supports environmentally friendly information dissemination and promotes sustainable geotourism education. This study highlights the potential of digital technology integration in strengthening educational functions within geopark areas and serves as a model for similar implementations in other geotourism destinations.